Gender economic inclusion, governance institutions and economic complexity in Africa - Ekene Emeka; Simplice Asongu; Yolande E. Ngoungou (African Governance and Development Institute (AGDI), 2024)
This study examines the effects of gender economic inclusion on economic complexity in Africa, as well as the moderating role of governance institutions on the relationship between gender inclusion and economic complexity. The analysis was based on the pooled OLS and the system generalized method of moments (GMM) estimation techniques, with data from 34 African economies between 2010-2021. The analysis uncovered several important findings. First, from the most robust model (i.e., GMM), positive synergies are apparent because gender economic inclusion promotes economic complexity, and governance dynamics further enhance the positive effect of gender economic inclusion on economic complexity. Second, regardless of the adopted technique, a predominantly positive and statistically significant relationship was identified between gender economic inclusion and economic complexity. Third, it was observed that while governance institutions exhibit a negative relationship with economic complexity, they play a positive role in moderating the relationship between gender inclusion and economic complexity. Fourth, factors such as foreign direct investment inflow, trade openness, and international tourism were identified as potent drivers of economic complexity in Africa, while the impact of human capital appears to be relatively subdued. Consequently, the study emphasizes the need for institutional reforms to improve governance transparency, accountability, and efficiency, alongside advocating for gender-inclusive policies and increased investment in education.
Keywords: G20; I10; I32; O40; O55; 330; Gender economic inclusion; economic complexity; governance institutions; panel data; Africa